Case Report: Electrode perforation with normal pacemaker parameters leading to hemorrhagic shock: a rare case report of the “penetration-exit-re-entry” phenomenon - Zuoan Qin; Jian Yang; Li Luo; Shi Chen; Fei Yang (Frontiers in Medicine, 2026)
Background Permanent pacemaker implantation via subclavian vein puncture may induce rare but life-threatening iatrogenic vascular injury. Vascular perforation with pacing lead penetration-exit-re-entry trajectory accompanied by normal intraoperative pacing parameters is reported extremely rarely, which greatly increases the risk of missed diagnosis. Case presentation A 70-year-old female patient with complete atrioventricular block received dual-chamber pacemaker implantation. All intraoperative lead electrical indicators were within normal range. Immediately after the operation, she rapidly developed massive hemothorax and hemorrhagic shock with severe hypoxemia. A thoracoscopic exploration verified a unique “penetration-exit-re-entry” lesion: the pacing electrode penetrated the left subclavian vein wall, exited the vascular lumen, and re-entered the innominate vein, resulting in persistent intrathoracic bleeding. After emergency thoracic drainage, surgical venous repair and blood transfusion resuscitation, the patient's vital signs gradually stabilized and fully recovered. A 1-month follow-up showed stable pacemaker function without adverse events. Conclusion This case highlights that normal intraoperative pacing parameters cannot rule out occult extravascular lead perforation and venous laceration. Operators should maintain high vigilance for unexplained perioperative hemodynamic collapse. Combined imaging, diagnostic thoracentesis, and early thoracoscopic surgical intervention are the core rescue strategies for this fatal complication.